2006
DOI: 10.1177/1354068806064730
|View full text |Cite
|
Sign up to set email alerts
|

Party Polarization in the US Congress

Abstract: Democrats and Republicans in the US Congress are as ideologically consistent and distinct as they have been at any point in the past three decades. Since 1973, the Senate has become 29 percent more polarized and House polarization has increased 47 percent. This investigation of party polarization finds that member adaptation accounts for one-third of the total party polarization in both the House and Senate. Member replacement accounts for the other two-thirds, the lion's share of which has been the replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(26 citation statements)
references
References 22 publications
2
22
0
2
Order By: Relevance
“…We chose to study state legislative politicians because of evidence that the same dynamics of asymmetric polarization persist at the state level and by the variation in contexts available in the states. Further, motivated by evidence that polarization is partly a function of newly elected candidates taking more extreme positions than their predecessors (Theriault 2006), we surveyed both incumbents and candidates. We measured these officeholders’ and candidates’ perceptions of public opinion in their districts across seven issues in total.…”
mentioning
confidence: 99%
“…We chose to study state legislative politicians because of evidence that the same dynamics of asymmetric polarization persist at the state level and by the variation in contexts available in the states. Further, motivated by evidence that polarization is partly a function of newly elected candidates taking more extreme positions than their predecessors (Theriault 2006), we surveyed both incumbents and candidates. We measured these officeholders’ and candidates’ perceptions of public opinion in their districts across seven issues in total.…”
mentioning
confidence: 99%
“…37 To be recognised as such, Indigenous groups must gather extensive documentation that they are internally 'homogenous', distinguished by their adherence to distinctive 'tribal' customs, historically 'resistant' to assimilation by foreign powers, and inclined to maintain the 'ecological balance' of their ancestral domains. 38 With these strings attached, indigeneity can constitute a disempowering 'burden of authenticity' 39 and risks shunting aside the most marginalised actors in favour of those who are most adept at navigating bureaucracy. 40 Oona Paredes, for example, has examined state efforts to identify Higuanon leaders in northern Mindanao and found that those with the greatest legitimacy among their fellows are often those who are least comfortable dealing with bureaucracy (and vice versa).…”
Section: Indigenous Rights In Practicementioning
confidence: 99%
“…Specifically, one could examine whether members of Congress's goals of serving their party conf licts with their goals of serving their constituents and creating good policy (Aldrich 1995;Aldrich andRohde 2000, 2001;Arnold 1990;Fenno 1978;Kingdon 1973Kingdon , 1977Kingdon , 2003Krehbiel 1993Krehbiel , 1998Mayhew 1974). Additionally, much Congressional research has examined legislator behavior in a highly polarized legislature (Fleisher and Bond 2004;Hetherington 2009;Layman, Carsey, and Horowitz 2006;Theriault 2006Theriault , 2008. Hypothetically, a member of Congress who finds his or her party's favored policies to be different from those of their constituents engages in more inauthentic surface acting or deep feeling to make voting decisions.…”
Section: Political Science: Emotion Management As Theory Adjudicatormentioning
confidence: 99%